Internalisasi Prinsip Tauhid Sebagai Fondasi Pendekatan Konseling Islam - Purnamawati, Agustin Mega; Kristina (Jurnal Ilmu Bimbingan dan Konseling, 2025)
Islamic counseling is a guidance and counseling approach rooted in Islamic teachings that aims to help individuals achieve holistic well-being encompassing psychological, spiritual, social, and moral dimensions. Unlike conventional counseling, which tends to emphasize cognitive and emotional aspects, Islamic counseling integrates spiritual values as a fundamental element in the helping process. The principle of tauhid (monotheism) serves as the main foundation that shapes an individual’s worldview of life, self-concept, and coping mechanisms in dealing with various life challenges. This article aims to examine the internalization of the principle of tauhid as a foundational paradigm in Islamic counseling through a literature review approach. The study analyzes classical and contemporary literature in the fields of Islamic theology, psychology, and counseling to understand the integration of tauhid values within the philosophical, ethical, and practical foundations of counseling. The findings indicate that tauhid functions as a philosophical foundation that gives meaning to human existence under divine guidance, an ethical foundation that fosters moral responsibility for both counselors and counselees, and a practical foundation that influences counseling techniques such as muhasabah (self-reflection), spiritual reflection, tawakkul (reliance on God), patience (sabr), and gratitude (shukr). The internalization of tauhid values significantly contributes to strengthening psychological resilience, reducing anxiety, and enhancing mental and spiritual well-being. Therefore, Islamic counseling based on tauhid offers a holistic, culturally relevant, and effective approach in addressing mental health challenges among Muslim communities in the modern era.